Tufted duck - Prestvannet Lake - Tromsø, Norway ... - Campbell, Sandy (University of Alberta Library, 2024)
Tufted ducks are one of the most common species at Prestvannet Lake in Tromsø, Norway. There were several pairs visible in early June. ...